(3QSGdI aj Yde GdaQGFVs - (3GdSgjdj , YHO GdQMef Hf YHO Gddg Hf CMeO Hf GUHZ GdNKYej CHh GdbGSe, CHh GdbGSe,J (B581 (3g` s
(3ChdgG (B:s
(3hHYO aEf Yde GdaQGFV dGjTJZd Hg GdG YGde QHGfi bGd GHf YHGS QVi Gddg Yfg s
(3BNQgG (B:s
(3ddUHGjg hGdUHG ai jOgG GdebSe CLeY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(Add 9625) s
Keywords: (3Yde GdaQGFVs